2005
DOI: 10.1055/s-0038-1632961
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete humeral condylar fracture in two English Pointer dogs

Abstract: Incomplete humeral condylar fracture was diagnosed by means of radiology, CT, scintigraphy, arthroscopy and bone biopsy in two English Pointer dogs. In both cases an acute thoracic limb lameness, unrelated to a known episode of major trauma, was observed. Incomplete humeral condylar fracture, mainly described in the Spaniel breeds, has been recently diagnosed in Labrador retrievers, Rottweiler, German Wachtel and other breeds. The pathogenesis of the condition is still unknown, but incomplete ossification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…Sclerosis adjacent to the intracondylar fracture site was a common finding in both breed groups. Sclerosis has been suggested to be an adaptive remodeling change to abnormal or excessive bone loading 14 . It is possible that abnormal loading is occurring through the humeral condyle in these dogs, but the aetiopathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sclerosis adjacent to the intracondylar fracture site was a common finding in both breed groups. Sclerosis has been suggested to be an adaptive remodeling change to abnormal or excessive bone loading 14 . It is possible that abnormal loading is occurring through the humeral condyle in these dogs, but the aetiopathogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The descriptive term HIF has been adopted and will be used for the remainder of this report. Humeral intracondylar fissures have been reported in several other breeds, more recently including the FBD 14–17 . A case series of 9 FBD presenting with HCF, found that six of nine dogs had a HIF identified on the limb contralateral to an HCF, suggesting that HIF could be a predisposing factor for HCF in this breed 18 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…5,25,26 Histopathological and clinical evidence has suggested HIF is a stress fracture rather than incomplete ossification of the humeral condyle. 1,18 Increased weight and activity have been suggested as predisposing factors for mechanical overload leading to stress fracture of the humeral condyle and may, in part, explain the higher proportion of male dogs affected. If humeroanconeal incongruency is occurring, increased muscle mass in male dogs may increase the force on contact between the humerus and anconeus and distracting force across the condyles.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] This is supported by histopathological findings on biopsy of the fracture line, which were more supportive of a fibrous, osteoclastic environment, similar to that of an atrophic non-union which may represent a stress fracture. 1,18 Ongoing biomechanical stress and instability have been hypothesized in patients with HIF following analysis of broken transcondylar screws by electron microscopy, and elbow incongruence has been suspected as a contributing factor to this stress. 13,19 More recently, humeroanconeal incongruency has been proposed as a possible contributing factor to HIF and ongoing intracondylar instability, following arthroscopic documentation of focal caudal humeral condylar cartilage lesions, adjacent to the apex of the anconeal process.…”
Section: Introductionmentioning
confidence: 99%